Fluid Mechanics and Machinery. - Kothandaraman, C. P. (New Age International Pvt. Ltd., Publishers, 2007)
About the Book: The text provides the following: Guidance in building of physical and mathematical models. Numerical examples for each of the equations derived numbering more than 100. Sketches and illustrations numbering more than 200. Solved problems to highlight whole spectrum of applications numbering more than 400. Objective questions for self evaluation numbering more than 700. Graded problems for exercise mostly with answers, numbering more than 450. Stress on validation of numerical results by counter checking. Contents: Physical Properties of Fluids Pressure Distribution.